Dynamics of drop impact onto a solid sphere: spreading and retraction. (10th July 2017) - Zhu, Yang; Liu, Hao-Ran; Mu, Kai; Gao, Peng; Ding, Hang; Lu, Xi-Yun
Abstract : In this paper, drop impact onto a sphere is numerically investigated at moderate Reynolds and Weber numbers. It is naturally expected that the aspect ratio of the sphere to the drop, [STIX]x1D706_r, would make a big difference to drop spreading and retraction on the sphere, compared with drop impact onto a flat substrate. To quantitatively assess the effect of [STIX]x1D706_r, a diffuse-interface immersed-boundary method is adopted after being validated against experiments. With the help of numerical simulations, we identify the key regimes in the spreading and retraction, analyse the results by scaling laws, and quantitatively evaluate the effect of [STIX]x1D706_r on the impact dynamics. We find that the thickness of the liquid film spreading on the sphere can be well approximated by h_L, ∞ (1+3/4[STIX]x1D706_r^-3/2), where h_L, ∞ represents the film thickness of drop impact on a flat substrate. At the early stage of spreading, the temporal variation of the wetted area is independent of [STIX]x1D706_r when the time is rescaled by the thickness of the liquid film. Drops are observed to retract on the sphere at a roughly constant speed, and the predictions of theoretical analysis are in good agreement with numerical results.